Semiotic square and narrative grammar in one first grade mathematical text - Kudžma, Ričardas; Rukaitė, Vitalija (Lietuvos matematikos rinkinys, 2014)
Analysis of narrative and logical-semantic levels according to Greimas‘s semiotics of concrete text from the first grade mathematics is presented in this article. Semiotic square is constructed and it is shown how moving in this square creates the meaning of the text.